Commercial gentrification in China and its distribution, development, and correlates: The case of Chengdu - Yang, Qinran; Liu, Yang; Yang, Linchuan (Frontiers in Environmental Science, 2022)
Commercial gentrification has often been treated as an attendant neighborhood phenomenon with residential gentrification in Anglo-American literature. This study aims to uncover the spatial pattern, development process and, most importantly, spatial correlations of commercial gentrification in Chengdu, a large Chinese city. With the data of points of interest, the study establishes the indicators of new retail places for emerging consumption for the Chinese new middle class, indicating the occurrence of commercial gentrification. Based on the methods of spatial and statistical analysis, its findings include: First, the distribution pattern of spaces for emerging consumption changed from a monocentric structure to a polycentric structure in the main urban areas of Chengdu from 2010 to 2020, with the largest core in the traditional commercial center. The high-tech zone of the city is a frontier of the development of the emerging retail spaces. Second, commercial gentrification in Chengdu has shifted from a centripetal development pattern to a centrifugal development pattern from 2010 to 2020. Spaces for emerging entertainment consumption grew most rapidly in the decade. Areas undergoing high-speed development are greatly influenced by local governments’ urban development strategies. Third, commercial gentrification was positively correlated with the growth of knowledge-intensive industries but negatively related to the change in both traditionally secondary and tertiary sectors in the past decade. Last, changes in housing prices showed no connection with commercial gentrification in the decade. The study suggests that commercial gentrification shall be treated as a phenomenon of industrial gentrification, independent of residential gentrification. More studies need to focus on the synergic and exclusive relations between commercial gentrification and the evolution of industrial spaces in the emerging post-industrial city economies.